Impact of a Protocol Change on Antibiotic Prescription for Acute Otitis Media in Children: A Retrospective Study in a Belgian Paediatric Emergency Department - Terrando, Till; Elise, Thielemans; Cavel, Oren; Roggen, Inge (Belgian Journal of Paediatrics, 2025)
Introduction: Acute otitis media (AOM) is a major driver of antibiotic use in children, though most cases are self-limiting. In October 2023, a revised protocol was introduced to align with national antibiotic stewardship guidelines. This study evaluated the impact of the protocol change on antibiotic prescribing and identified factors associated with prescription decisions. Methods: We conducted a retrospective cohort study of children aged 3 months to 16 years diagnosed with AOM during two six-month periods: before (PRE) and after (POST) protocol implementation. Patients with comorbidities, prior antibiotic use, or incomplete records were excluded. Logistic regression was used to assess the effect of the protocol and clinical variables on systemic and local antibiotic use. Results: Of 1,868 visits, 1,669 were included (905 PRE, 764 POST). Systemic antibiotic prescriptions decreased significantly from 59.0% to 46.6% (p < 0.001). POST-period presentation was associated with lower odds of systemic antibiotic use (OR = 0.59; 95% CI: 0.43–0.81). Factors increasing systemic antibiotic use included younger age and clinical red flags. Five-day treatment courses rose from 16.2% to 45.2%, while delayed prescriptions increased modestly. Overall local antibiotic use remained stable. Older children were more likely to receive local treatment. Conclusion: The revised protocol significantly reduced systemic antibiotic use and encouraged shorter, more targeted treatments. Further education is needed to limit unnecessary local antibiotic use.